A grammar, Armenian and English - Aukerian, Haroutiun, 1774-1854 (My University, 1832)
"A Grammar, Armenian and English" by Haroutiun Aukerian (P. Paschal Aucher) is a foundational text for learning Classical Armenian. This historic volume provides a comprehensive overview of Armenian grammar, designed for English speakers
By P. Paschal Aucher D.D. (Աւգերեան Յարութիւն). - Venice, Armenian press of St. Lazarus, 1832.- 230 p., 1 l., 20 cm.
https://www.loc.gov/item/11028047/
Keywords: Armenian language-Grammar